Environmental Factors Related to The Incidence of Acute Bronchitis in the Work Area of the Batu Tunggal Community Health Center - Ni'matul Ulya Munthe; Yulia Khairina Ashar; Achyar Zein; Nofi Susanti; Susilawati Susilawati (PROMOTOR, 2026)
Acute bronchitis in the operational area of the Batu Tunggal Community Health Center UPTD has developed, initially 423 cases in 2023, growing to 636 cases in 2024. The purpose of this study is to determine what environmental factors are related to the incidence of acute bronchitis in the Batu Tunggal Community Health Center UPTD Working Area. This study is a quantitative study using a case control design. The study case population is 190 cases, with a sample of 56 respondents divided into 28 case groups and 28 control groups, and data collection using a questionnaire instrument. Testing was carried out using the Chi-Square statistical test with SPSS 20. The findings of this study found that there was a relationship between the Residential Density Variable (p-value = 0.030; OR = 4.000), and Cigarette Smoke Exposure (p-value = 0.027; OR = 4.231) with the incidence of Acute Bronchitis in the Batu Tunggal Community Health Center UPTD Working Area. Meanwhile, the variables of occupation (p-value = 1.000; OR = 0.641) and history of allergies (p-value = 1.000; OR = 1.000) did not have a relationship with the incidence of acute bronchitis in the work area of the Batu Tunggal Community Health Center UPTD. Suggestions for health workers to conduct more effective outreach to the community to increase public knowledge.